Electrospun cellulose acetate nanofibers for airborne nanoparticle filtration. Issue 15 (August 2019) - Ahne, Joerg; Li, Qinghai; Croiset, Eric; Tan, Zhongchao
Reported in this paper are the effects of tip-to-collector distance, voltage, deposition time and solution concentration on the fiber size distribution and filter quality factor of electrospun cellulose acetate (CA)-based nanofibers. Nanofibrous filter samples were produced by electrospinning in a laboratory setting. The CA solutions were prepared by diluting various concentrations of CA in a 2:1 (w:w) ratio of N, N-dimethylacetamide (concentration 10–20 wt.%). The electrospinning voltages ranged from 8–12 kV, with distances from 10–15 cm and deposition times of up to 30 minutes. The produced nanofibrous filter samples were then analyzed in terms of fiber size distribution and filter quality factor using nanosized sodium chloride particles ranging from 4–240 nm in diameter. The maximum filtration efficiency measured was 99.8% for filter samples obtained with an overall deposition time of 30 minutes. The maximum filter quality factor was 0.14 Pa −1 for a CA concentration of 20 wt.% and a tip-to-collector distance of 15 cm. The average fiber diameters of the fibers were between 175 and 890 nm, and CA concentrations below 15% led to the formation of beads.